Effects of valsartan on morphine tolerance and dependence in rats - Ayat Kaeidi; Morteza Amirteimoury; Mohammad-Saleh Zare; Amirhossein Nazari; Elham Hakimizadeh; Jalal Hassanshahi; Iman Fatemi (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Opiates are traditionally used for the treatment of pain. Chronic consumption of opiates such as morphine (MOR) induces tolerance and dependence. This study aimed to investigate the effects of valsartan (VAL), as an angiotensin II receptor blocker, on the induction and expression of MOR analgesic tolerance and physical dependence in rats. Experimental approach: MOR 10 mg/kg was injected s.c. twice a day for 7 days to induce tolerance and dependence. For evaluating the effect of VAL on the induction of MOR analgesic tolerance and physical dependence, 20 mg/kg VAL was administered orally (once a day) during the 7 days of the examination period. The tail-flick test was performed every day. On day 7, 5 mg/kg naloxone () was injected s.c. into the morphine-dependent rats and the rats were monitored for 30 min for the frequency of withdrawal signs such as jumping, diarrhea, defecation, head tremor, rearing, scratching, sniffing, teeth chattering, and wet-dog shake. For evaluating the effect of VAL on the expression of MOR-analgesic tolerance and physical dependence, 45 min before the last MOR injection, VAL was administered only on day 7. The tail-flick test was performed and naloxone was injected into the addicted rats and they were monitored for 30 min for the frequency of withdrawal signs such as jumping, diarrhea, defecation, head tremor, rearing, scratching, sniffing, teeth chattering, and wet-dog shake. Findings/Results: Our results revealed that the co-administration of VAL with MOR for 7 consecutive days reduced the induction of MOR tolerance. Moreover, VAL administration for 7 days along with MOR reduced the frequency of diarrhea and defecation in naloxone-injected animals. Conclusion and implications: According to the results presented in this study, chronic administration of VAL prevented the induction of MOR-analgesic tolerance and dependence in rats.